Kinetic patterns of benign and malignant breast lesions on contrast enhanced digital mammogram. - Jer-Shyung Huang; Huay-Ben Pan; Tsung-Lung Yang; Bao-Hui Hung; Chia-Ling Chiang; Meng-Yuan Tsai; Chen-Pin Chou (PLoS ONE, 2020)
Purpose To evaluate the kinetic patterns of benign and malignant breast lesions using contrast-enhanced digital mammogram (CEDM). Methods Women with suspicious breast lesions on mammography or ultrasound were enrolled. Single-view mediolateral oblique (MLO) CEDM of an affected breast was acquired at 2, 3, 4, 7, and 10 min after injection of contrast agent. Three readers visually and semi-quantitatively analyzed the enhancement of suspicious lesions. The kinetic pattern of each lesion was classified as persistent, plateau, or washout over two time intervals, 2-4 min and 2-10 min, by comparing the signal intensity at the first time interval with that at the second. Results There were 73 malignant and 75 benign lesions in 148 patients (mean age: 52 years). Benign and malignant breast lesions showed the highest signal intensity at 3 min and 2 min, respectively. Average areas under receiver operating characteristic (ROC) curve for diagnostic accuracy based on lesion enhancement at different time points were 0.73 at 2 min, 0.72 at 3 min, 0.69 at 4 min, 0.67 at 7 min, and 0.64 at 10 min. Diagnostic performance was significantly better at 2, 3, and 4 min than at 7 and 10 min (all p < 0.05). A washout kinetic pattern was significantly associated with malignant lesions at 2-4 min and 2-10 min frames according to two of the three readers' interpretations (all p ≤ 0.001). Conclusion Applications of optimal time intervals and kinetic patterns show promise in differentiation of benign and malignant breast lesions on CEDM.